Conformez-vous!: Les resistances et contestations á la marchandisation du savoir dans I' université néolibérale (2017)
This article is the result of the reflections and debates that have been generated about the contemporary university at the Doctoral Seminar in Political Science at the Université du Québec à Montréal. The economic and political changes of the 1970s stimulated a reorganization of the knowledge production process. In order to adapt to the new socio-political context of market liberalization and state efforts to establish the competitiveness of national economies, universities have had to undergo a major restructuring. The neoliberal university is then characterized by a demand for increased productivity, by budget cuts, by the accumulation of administrative tasks for teachers as well as by a commercialization of knowledge. In this sense, this article aims to question the neoliberalisation of the contemporary university and the practical transformations that characterize it in order to propose ways of thinking about the possible resistance to precariousness of the institution by the system. neoliberal. It presents a brief context on the emergence of the neoliberal university and the characteristics of this type of university. In a second step, the article tackles ways of resistance to the commercialization of knowledge and, finally, it proposes a reflection on the contestation of the hegemonic knowledges. In short, the article invites the questioning of the productivity logic underlying the neoliberal university and hides a system of homogenization of thought that contributes to the construction of hegemonic knowledge leading to the marginalization of subordinate knowledge.